Chitosan membranes for spatially controlled cell adhesion and specific cell recruitment - Custódio, Catarina A. (2012)
We propose a concept of biomaterials that are able to fix specific cell types onto their surface when in contact with a mix population of cells. Adipose tissue has shown to be an interesting source of stem cells with therapeutic potential. However only a small amount of the heteroge- neous mixture of the cells extracted from lipoaspirates are stem cells, and within stem cells there are different populations with different capabilities to differentiate through a lineage. We studied the ability of immobilized antibodies on chitosan surfaces to capture specific types of cells with a spatial micrometer resolution.Antibodies were covalently immobilized onto chitosan membranes using bis[sulfosuccinimidyl] su- berate (BS3). X-ray photoelectron spectroscopy (XPS) was used to chemically characterize the surface and quartz crystal microbalance (QCM) to calculate the amount of adsorbed and/or immobilized anti- body. Data shown greater immobilization when BS3 was used com- pared to simple adsorption. Specific antibodies covalently immobilized in a surface, kept their bioactivity and controlled the type of cell that attached on the chitosan surface. Microcontact printing permitted to covalently immobilize antibodies in patterns allowing a spatial control in cell attachment. Cell sorting experiments performed using a mixture of adipose stem cells and osteoblast like cells shown that chitosan sur- faces were able to capture a specific phenotype depending on the immobilized antibody.